Unveiling the Impact of Three-Dimensional Technology on Rhinoplasty: A Systematic Review and Meta-analysis - Werathammo, Methini; Seresirikachorn, Kachorn; Charoenlux, Prapitphan (Facial Plastic Surgery, 2024)
This study aimed to investigate the impact of three-dimensional (3D) technology on preoperative evaluation for rhinoplasty.A systematic search was conducted on Embase, MEDLINE, and Web of Science. Studies that utilized 3D technology in preoperative assessment for rhinoplasty were included. The primary outcome was surgeon and patient satisfaction. The secondary outcomes included nasal function, cost-efficiency, reoperation rate, precision, and surgical time.Twelve studies (595 patients) were included. Surgeons reported higher satisfaction with 3D approaches based on precision and postoperative results. Patients expressed satisfaction with the 3D approaches due to a better understanding of the procedure and the ability to discuss with the surgeons planning the procedure and participating in postoperative design. The 3D approaches demonstrated higher surgeon satisfaction (mean difference −0.13, 95% confidence interval [CI] −0.20 to −0.06, p = 0.0002), particularly in revision cases, and provided higher precision compared with the two-dimensional (2D) approaches. However, 3D technology was more expensive and not cost-efficient. There were no significant differences in reoperation rate (odds ratio 0.16, 95% CI 0.02–1.36, p = 0.09) and surgical time. Postoperative nasal function showed inconsistent results.3D technology offered higher surgeon satisfaction and increased precision compared with 2D imaging. However, 3D imaging was expensive and not cost-efficient. Reoperation rate and surgical time were comparable, while postoperative nasal function outcomes showed inconsistent results.
Keywords: rhinoplasty; 3D photography; 3D simulation; 3D printing; 3D technology